Layanan Bimbingan dan Konseling dalam Mengatasi Kesulitan Belajar Siswa Kelas V SD Inpres Sambiki Kecamatan Morotai Timur - Amrin Sibua (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study examines guidance and counseling assistance in overcoming learning difficulties of fifth grade students of SD Sambpres Inpres. The focus of this study discusses the factors that cause learning difficulties of fifth grade students of SD Inpres Sambiki and the discussion of guidance and counseling services in overcoming learning difficulties of fifth grade students of SD Inpres Sambiki. This type of research used in this research is descriptive qualitative research, case study studies. The selection of subjects was done by purposive sampling, namely the fifth grade elementary school teacher Sambpres Inpres, some students who had difficulty learning and several teachers related to this study. Data collection by interview, documentation, and observation. Data analysis process, namely: Data reduction, data display, and drawing conclusions / verification. The results showed that the teacher had not made a structured guidance and counseling service program. Tutoring services are carried out by class V teachers in accordance with the teacher's understanding of the concept of guidance and counseling services. Implementation of guidance and counseling services by teachers to help students in class V to achieve learning goals according to the specified targets and not on overcoming problems and difficulties faced by students during the learning process. Tutoring services implemented by the teacher do not match the concept requested. In implementing tutoring services, teachers use the method of improvement and enrichment.